The mental health of young children with intellectual disabilities or borderline intellectual functioning - Stancliffe, R; Einfeld, S; Emerson, Eric (My University, 2010)
Objective To determine within a nationally representative sample of young Australian children: (1) the association amongst intellectual disability, borderline intellectual functioning and the prevalence of possible mental health problems; (2) the association amongst intellectual disability, borderline intellectual functioning and exposure to social disadvantage; (3) the extent to which any between-group differences in the relative risk of possible mental health problems may be attributable to differences in exposure to disadvantageous social circumstances. Methods The study included a secondary analysis of a population-based child cohort of 4,337 children, aged 4/5 years, followed up at age 6/7 years. The main outcome measure was the scoring within the ‘abnormal’ range at age 6/7 years on the parent-completed Strengths and Difficulties Questionnaire. Results When compared to typically developing children, children identified at age 4/5 years as having intellectual disability or borderline intellectual functioning: (1) showed significantly higher rates of possible mental health problems for total difficulties and on all five SDQ subscales at age 6/7 years (OR 1.98–5.58); (2) were significantly more likely to be exposed to socio-economic disadvantage at age 4/5 and 6/7 years. Controlling for the possible confounding effects of exposure to socio-economic disadvantage (and child gender) significantly reduced, but did not eliminate, between-group differences in prevalence. Conclusions Children with limited intellectual functioning make a disproportionate contribution to overall child psychiatric morbidity. Public health and child and adolescent mental health services need to ensure that services and interventions fit to the purpose and are effective for children with limited intellectual functioning, and especially those living in poverty, as they are for other children.
Social Psychiatry and Psychiatric Epidemiology
Keywords: Health; Children; Health -- Mental; Health -- Disability; Children -- Disabled; Health and wellbeing; Children; Health; Mental; Disabled; Disability; Health and wellbeing